Severe lymphopenia in tuberculosis: a mere coincidence or a significant association? - Gönç, E. Nazlı; Özen, Seza; Göçmen, Ayhan; Zafer, Yeşim; Tezcan, İlhan (The Turkish Journal of Pediatrics, 2000)
A variety of infectious agents can cause secondary immunodeficient states. We herein present a one-year-old patient, admitted to the hospital with severe lymphopenia, who was subsequently diagnosed as tuberculosis. After the antituberculosis (anti TB) therapy was started, the clinical condition and the immunologic findings of the patient improved. We have thus concluded that the transient lymphopenia of the patient was due to Mycobacterium tuberculosis. We suggest that immunodeficiency should be investigated more often in children with tuberculosis and that further studies will shed light on the pathogenesis of this aspect of the disease.
Keywords: childhood; lymphopenia; tuberculosis